The Relevance of The Character Education Development Model in Islamic Boarding Schools - Dandy Sobron Muhyiddin; Dodo Suhada; Mohamad Yamin; Bambang Samsul Arifin; Aan Hasanah (Program Studi Pendidikan Islam, 2022)
Formal educational institutions in Indonesia, carrying out character education in Indonesia, the implementation is carried out by formal education units that follow the program launched by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) and the Ministry of Religion (Kemenag). Meanwhile, Islamic boarding schools in Indonesia, as independent educational institutions, have basically implemented character education with their concepts. Islamic boarding schools are considered traditional institutions but still attract public interest. Among the advantages possessed by Islamic boarding schools so that they are in demand by the public is that they are considered to have advantages in terms of character education, this is evidenced by the application of the Islamic boarding school curriculum that is independent, not co-opted with any party including the government (Kemendikbudristek/Kemenag). Furthermore, this independent nature is also proven that every Islamic boarding school in Indonesia has a unique curriculum, different from one another. In general, the curriculum applied in Islamic boarding schools is through the study of classical books or better known as the yellow book. As a result, the development of character education models in Islamic boarding schools in Indonesia is based on integrated yellow book studies in the context of tafaqquh fiddiin and seeks to realize it in the form of daily practice with refraction and training accompanied by exemplary examples from teachers/ustadz/kyai.